2005
DOI: 10.1007/s00056-005-0509-1
|View full text |Cite
|
Sign up to set email alerts
|

Dental Care with Manual Toothbrushes during Fixed Orthodontic Treatment—a New Testing Procedure

Abstract: From testing five toothbrushes with four different weights, we have established profiles confirming the beneficial and less beneficial properties of certain toothbrushes involving various high contact forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The fi ndings ( Figure 4 ) confi rm the results of a previous in vitro study ( Sander et al , 2005 ) which showed that different bristle arrangements, such as lowered bristles in the middle of the brushfi eld, have improved cleaning effi cacy than planar bristle fi elds. Toothbrushes with a fl at profi le proved to be unsatisfactory for the cleaning of teeth with brackets.…”
Section: Discussionsupporting
confidence: 85%
“…The fi ndings ( Figure 4 ) confi rm the results of a previous in vitro study ( Sander et al , 2005 ) which showed that different bristle arrangements, such as lowered bristles in the middle of the brushfi eld, have improved cleaning effi cacy than planar bristle fi elds. Toothbrushes with a fl at profi le proved to be unsatisfactory for the cleaning of teeth with brackets.…”
Section: Discussionsupporting
confidence: 85%
“…At a high load, soft or fine bristles may become twisted resulting in a lower cleaning efficacy. With low force, interaction with the toothsurfaces increases since soft bristles allow penetration into the interproximal and interbracket area (Sander et al, 2005). To overcome this phenomenon and to assess the effect of various high contact forces, the pressure (load/brush field surface) in the present study was kept constant.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to facilitate plaque control in orthodontic patients, specially designed manual and electric toothbrush heads have been marketed. For manual toothbrushes, experimental studies have shown that staged and V-shaped brush head designs outperformed planar brushes in the cleaning efficacy of teeth with fixed orthodontic attachments (Sander et al, 2005;Schätzle et al, 2009). Their effectiveness in clinically reducing gingivitis is, however, questionable (Williams et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations